Feasibility Assessment for Developing a Mobile Applications Sector in Afghanistan - World Bank (Washington, DC, 2014)
Afghanistan has made significant progress in its development since 2001. Yet, these achievements remain continually fragile because of a volatile security situation and limited human capacity. In spite of these constraints, the information and communications technology (ICT) sector in the country has witnessed remarkable growth. The study estimated that the mobile app market will grow from its estimated $20-$33 million to $48-$60 million, at least twice the current size in the next three years. Gaps include lack of relevant skills and experience needed for the mobile app market (and also absences in resources needed to provide these skills), a deficiency in the awareness of the potential of mobile technology, and barriers because of the use of multiple languages and low levels of English language fluency. Methods to access the end user of mobile products remain nonexistent. The study notes that increased awareness, relevant skills, and access to practical experience in the mobile industry are a top priority. As such developers need access to tools that are localized. Finally, an alternative application distribution mechanism, which enables access to a greater market and capacity to bill services, is essential. The study underscores the importance of leveraging the existing government initiatives: an ICT incubator and related programs funded through the World Bank Group, other donor driven programs providing access to funding, and locally driven grassroots programs supporting awareness raising. To address the problem of end-user access, the study offers a game-changing proposal to establish an app store that is built locally and provides locally relevant content. The app store can raise further awareness and build a pipeline of entrepreneurs and users to further drive the mobile market. The report attached provides a synopsis of the mapping of the ecosystem and a survey of current initiatives and existing gaps. Recommendations and a roadmap for designing future programs targeting mobile entrepreneurs are also included in the report. The subsequent PowerPoint offers a unique presentation of the analysis and results for this specific study.